Being a presence for students : teaching as a lived defense of liberal education - Frank, Jeff, 1980- (Lever Press, 2019)
"This book offers a lived defense of liberal education. How does a college professor, on a daily basis, help students feel the value of liberal education and get the most from that education? We answer this question, as professors, each day in the classroom. John William Miller, a philosophy professor at Williams College from 1924-1960 and someone noted for his exceptional teaching, developed one form that this lived defense can take. Though Miller published very little while he was alive, the archives at Williams College hold unpublished notes and essays of this master teacher. In this book, Jeff Frank offers an extended commentary on one of these unpublished essays where Miller develops his thinking on liberal education. Frank develops the idea that presence is central to liberal education and offers suggestions for how professors can become an educative presence for students. The goal of this book is an invitation to other professors who value liberal education to think with Miller about how to develop their own lived defense of liberal education, each day, in their own classrooms. The tone of the book is meant to be invitational, at times even conversational, and the book concludes with some direct suggestions for how professors can live their own defense of liberal education."--Title screen